Pengembangan Aplikasi Edukasi Seksual untuk Remaja dengan Metode Kuis berbasis Progressive Web App - Alfonsus Avianto Chandrawan; Fais Al Huda; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Sexual education is still often considered taboo by most Indonesian people. A survey conducted by Durex Indonesia shows that 84 percent of Indonesian teenagers have not received sexual education. In fact, it is very essential for sex education to be taught to teenagers, especially when they are entering adolescence. A sexual education application named